Opioid-induced respiratory depression and risk factors in a tertiary hospital: A retrospective study - Nabil A. Almouaalamy; Majed Alshamrani; Waleed K. Alnejadi; Ziyad M. Alharbi; Faisal M. Aldosari; Enad F. Alsulimani; Saif A. Saif; Mohammed K. Aldawsari (Elsevier, 2022)
Background: Opioids are potent analgesics used for the treatment of moderate to severe acute and chronic cancer and non-cancer pain. However, opioid usage may be limited by negative side effects, such as potentially life-threatening respiratory depression. Objectives: The aim of our study is to investigate the prevalence of opioid-induced respiratory depression (OIRD) and its predictors at King Abdulaziz Medical City in Jeddah (KAMC-JD). Method: This is a retrospective cross-sectional (chart review) study conducted from January 1, 2016, to December 31, 2020. Results: A total of 15,753 patients received opioids during admission to KAMC-JD, and only 144 (0.915%) of them received naloxone from January 1, 2016 to December 31, 2020. Only 91 patients (0.57%) developed opioid-induced respiratory depression (OIRD), which was more frequently reported among young and middle-aged adults. OIRD was significantly associated with receiving a daily morphine milligram equivalent (MME) dose of ≥150 MME and with having a low urea concentration at the baseline and at admission under surgery. Also, fentanyl use remained a significant risk factor for OIRD. Conclusion: In conclusion, monitoring patient receiving opioids with a daily MME dose of ≥150 MME, prescribed Fentanyl, low urea concentration at the baseline, and patients' admissions to the surgery department may mitigate the risk of developing OIRD.